Research Trends on Guided Inquiry Models to Improve Students' Critical Thinking Skills in Science Learning: A Bibliometric Analysis - Putri, Windiarti Pratiwi (Balai Publikasi Indonesia, 2025)
This research explores the influence of guided inquiry through bibliometric analysis using the Publish or Perish, VOSviewer, and Dimensions tools. Utilising overlay, density, and network visualisations, this study identified key research trends, relationships between concepts, and frequency density of terms in the literature related to guide inquiry. The results of the analysis showed that publications related to guided inquiry on improving critical thinking skills have increased, with articles and Proceedings being the most dominant forms of publications. These findings suggest that guided inquiry not only supports more flexible science learning, but also to improve students' critical thinking skills in various subject areas.